Scaphometacarpal Space and Postoperative Outcomes: A Systematic Review - Rezzadeh, Kevin; Donnelly, Megan; Daar, David; Hacquebord, Jacques (Journal of Wrist Surgery, 2020)
Background A common notion is that more complex techniques for treating trapeziometacarpal arthritis such as ligament reconstruction and tendon interposition (LRTI) better preserve the scaphometacarpal (SMC) space compared to a simple trapeziectomy and that this leads to superior functional outcomes.Purpose The purpose of this systematic review is to evaluate the relationship between scaphometacarpal space and objective outcomes such as grip and pinch strength as well as subjective patient-reported outcomes.Methods A systematic review of the literature was conducted according to PRISMA guidelines. Inclusion criteria were studies reporting SMC space and outcomes after surgery for carpometacarpal arthritis. The primary outcomes of these studies included any measure of postoperative scaphometacarpal space (trapezial height/trapezial index) as well as key pinch strength, grip strength, or lateral pinch strength. Studies that did not assess for association between SMC space and outcomes were excluded.Results Fourteen studies were included in this systematic review. Three (21.4%) studies found a statistically significant correlation between postoperative SMC space and postoperative pinch or grip strength. The correlation was weakly positive in one study (key pinch vs. scaphometacarpal space, r = 0.13), positive but unlisted in another (lateral pinch vs. trapezial ratio), and negative in the third study (key pinch vs. trapezial space ratio, r = −0.47).Conclusion Preservation of the SMC space postoperatively is not associated with postoperative outcomes. Further research is necessary to better characterize the importance of maintaining the SMC space in patients undergoing LRTI in order to substantiate claims by proponents of the procedure.
Keywords: scaphometacarpal space; trapeziectomy; CMC arthritis; LRTI